The Role of Topical Treatment on Vaginal Tightening - Hendaria, Made Putri; Maylita Sari (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Physiological changes in a woman's life, such as labor, weight fluctuations, hormonal changes, aging, and menopause, cause changes in both appearance and function of the vagina. As estrogen deficiency continues, changes occur in the form of atrophy and dystrophy in the vaginal mucosa, vulva, and other structures in the urogenital tract which are called symptoms of vulvovaginal atrophy. It affects women's quality of life, self-confidence, and sexuality. As alternative modality for noninvasive therapy, topical therapy in vaginal rejuvenation is becoming available in the care of outpatients. This makes it increasingly important for dermatologists to be well-informed about these treatment options. Purpose: This review aims to assess the role of topical therapy in vaginal rejuvenation, especially in vulvovaginal atrophy cases. Literature Review: Vulvovaginal atrophy has a negative effect on interpersonal relationships, quality of life, daily activities, and sexual function. Topical hormone replacement therapy includes all preparations such as estradiol, estradiol valerate, or conjugated estrogen. considered in cases with vulvovaginal atrophy accompanied by atrophy of the urogenital system as well as the accompanying complaints because this therapy is intended to prevent systemic complications. The topical use of hyaluronic acid, lubricants, moisturizers, and herbs is a therapeutic choice in vulvovaginal atrophy patients contraindicated with estrogen therapy or in patients who do indeed choose nonhormonal therapy. Conclusion: Topical therapy of hormonal and non-hormonal rejuvenation in various studies has shown improvement in symptoms of vaginal dryness, vaginal itching, dyspareunia, cell maturity, and changes in vaginal pH toward acidity.